Cover Picture: Tomographic Reconstruction of Designer Free‐Electron Wave Packets (ChemPhysChem 7/2013). Issue 7 (29th April 2013) - Wollenhaupt, Matthias; Lux, Christian; Krug, Marc; Baumert, Thomas
<x xml:space="preserve">Abstract</x> Designer electron wave packets are created by multiphoton ionization of potassium atoms employing polarization‐shaped femtosecond laser pulses, as reviewed on p. 1341 by M. Wollenhaupt et al. In order to reconstruct the three‐dimensional photoelectron momentum distribution, we use a velocity‐map imaging spectrometer to measure multiple projections at different angles by rotating the pulse with a l/2 plate. This procedure is illustrated for elliptically polarized light in the lower row. The images along the arrows (top left) show the evolution of measured projections towards a prescribed target (T) during an iterative optimization of the polarization‐shaped pulse.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>